2019
DOI: 10.3238/arztebl.2019.0553
|View full text |Cite
|
Sign up to set email alerts
|

Functional Somatic Symptoms

Abstract: on behalf of the guideline group "Functional Somatic Symptoms"* T he German clinical practice guideline on the management of patients with unspecific, functional, and somatoform physical symptoms (1, 2) expired in March 2017. Between November 2016 and July 2018, the guideline was updated and thoroughly revised by a group under the coordination of the German College of Psychosomatic Medicine (Deutsches Kollegium für Psychosomatische Medizin, DKPM) and the German Society of Psychosomatic Medicine and Medical Psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
23

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 137 publications
(9 reference statements)
3
27
0
23
Order By: Relevance
“…In terms of comorbidities, FSS are associated with psychiatric disorders, with high rates of depressive and anxiety symptoms [ 4 , 9 ], which was corroborated by the current study, which found a significant association between all psychopathological symptoms and the FSS severity, with anxiety symptoms having the highest correlation coefficient in both groups. In addition, a significant correlation ( p < 0.001) was found between the severity of somatic symptoms and obsessive-compulsive symptoms, psychoticism, and paranoid ideation, which is in accordance with previous studies that point out that personality disorders are associated with severe FSS [ 38 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In terms of comorbidities, FSS are associated with psychiatric disorders, with high rates of depressive and anxiety symptoms [ 4 , 9 ], which was corroborated by the current study, which found a significant association between all psychopathological symptoms and the FSS severity, with anxiety symptoms having the highest correlation coefficient in both groups. In addition, a significant correlation ( p < 0.001) was found between the severity of somatic symptoms and obsessive-compulsive symptoms, psychoticism, and paranoid ideation, which is in accordance with previous studies that point out that personality disorders are associated with severe FSS [ 38 ].…”
Section: Discussionsupporting
confidence: 87%
“…Functional somatic symptoms (FSS) refer to persistent bodily symptoms that lead individuals to seek health care, and that no organic pathology is found that explains such symptoms [ 1 , 2 , 3 , 4 ]. FSS are common in medical practice and have frustrated doctors and patients as it is a diffuse condition, difficult to treat, and that can cause considerable disability [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the provision of self-help information has been shown to improve the quality of life of IBS patients 32 , thus reducing the need for further consultation. Additionally, the Gemran FSS guideline advocates for restraint in diagnostic investigations when somatoform disorders are suspected 33 . Of those patients whose FSS diagnosis is confirmed in two quarters, there is a moderately high persistence, with between one third and two thirds of patients receiving the same diagnosis after five years.…”
Section: Discussionmentioning
confidence: 99%
“…Hierzu analysierte die Leitliniengruppe nach systematischer Literaturrecherche 3795 neue Originalarbeiten und 3345 systematische Reviews, von denen 358 Publikationen in die Aktualisierung Eingang fanden. Im fast durchgehend starken Konsensus wurden evidenzbasierte Empfehlungen, Hintergrundinformationen und klinische Entscheidungshilfen für Diagnostik und Therapie erarbeitet und so eine aktuelle, interdisziplinäre, evidenzbasierte, praxisnahe und anwenderfreundliche klinische Leitlinie erstellt [3,4]. Zusätzlich wurden für dieses narrative Review, basierend auf einer selektiven Literaturrecherche in PubMed/MEDLINE, einschlägige ältere Arbeiten herausgegriffen und besonders relevante neuere Arbeiten ergänzt, vor allem systematische Reviews und Meta-Analysen.…”
Section: Hintergrund Und Methodikunclassified